2023
DOI: 10.3390/mi14091772
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspiration and Biomimetic Art in Robotic Grippers

Van Pho Nguyen,
Sunil Bohra Dhyan,
Vu Mai
et al.

Abstract: The autonomous manipulation of objects by robotic grippers has made significant strides in enhancing both human daily life and various industries. Within a brief span, a multitude of research endeavours and gripper designs have emerged, drawing inspiration primarily from biological mechanisms. It is within this context that our study takes centre stage, with the aim of conducting a meticulous review of bioinspired grippers. This exploration involved a nuanced classification framework encompassing a range of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 266 publications
0
4
0
Order By: Relevance
“…Drawing inspiration from the elephant trunk in our design, we initiate our exploration by delving into various trunk models, such as the kinematic continuum model presented by Wilson [4] and the dynamic model articulated by Mishra [5]. Over the years, numerous robotic systems have been developed, all inspired by elephant trunks, ranging from shape memory, alloy-based systems [6] to more complex mechanisms like the one presented by Huang [7], and even different types of unique grippers [8]. These works collectively underscore the inherent advantages of the elephant trunk and demonstrate how a manipulator inspired by such principles can reap similar design benefits.…”
Section: Related Workmentioning
confidence: 99%
“…Drawing inspiration from the elephant trunk in our design, we initiate our exploration by delving into various trunk models, such as the kinematic continuum model presented by Wilson [4] and the dynamic model articulated by Mishra [5]. Over the years, numerous robotic systems have been developed, all inspired by elephant trunks, ranging from shape memory, alloy-based systems [6] to more complex mechanisms like the one presented by Huang [7], and even different types of unique grippers [8]. These works collectively underscore the inherent advantages of the elephant trunk and demonstrate how a manipulator inspired by such principles can reap similar design benefits.…”
Section: Related Workmentioning
confidence: 99%
“…To this end, we aimed to develop soft robotic grippers with bio-inspired grasping efficiency. Authors in [1][2][3][4][5][6] reported many natural adhesion mechanisms with potential for application to robotic manipulation. Soft grippers proposed by other authors [7][8][9][10][11][12] could handle several food samples.…”
Section: Introduction 1relating Work In Soft Grippersmentioning
confidence: 99%
“…The advantage of bioinspired soft grippers (compared to traditional rigid grippers) lies in their ability to handle delicate and irregularly shaped objects [20]. This makes them invaluable in applications like smart actuators, flexible electronics, robotic surgery, health care, and prosthetics-where precision and adaptability are essential [17,21,22].…”
Section: Introductionmentioning
confidence: 99%